A rare case report of hyaline-vascular type Castleman disease in the presacral region - Chang, Long; Wang, Shuang; Li, Jiannan; Zhao, Zeyun; Wang, Min (Frontiers in Oncology, 2024)
Castleman disease (CD), also known as giant lymph node hyperplasia or angiofollicular lymph node hyperplasia, is a rare and indeterminate group of chronic lymphoproliferative disorders. CD is highly heterogeneous, classified into unicentric Castleman disease (UCD) and multicentric Castleman disease (MCD) based on lesion distribution, and further categorized into three pathological types: hyaline vascular type (HV), plasma cell type (PC), and mixed type (Mix). This paper describes a rare case of solitary mediastinal Castleman disease with transparent vessels in the anterior sacrum, presenting as the HV type. Surgical excision of the mass was performed following coccygectomy for treatment. The patient recovered well postoperatively. During a 6-month follow-up period, there were no signs of recurrence, and the patient's quality of life significantly improved.